Arrangement for Issuance of Certificate of Substitute of Land Rights - Yana Ardila; Julianto Jover Jotam Kalalo (Faculty of Law, Musamus University, 2019)
The certificate is used as a valid and strong proof if there is a problem in the future. Problems are not just about land disputes, but problems such as certificates that have been issued are damaged due to not being cared for properly, the paper is damaged due to obsolescence, then natural disasters occur that sweep away or burn the certificate, and disappear due to theft or self-negligence. For that reason, the people whose certificates have been lost, damaged and so on are obliged to come to the office of the National Land Agency (BPN) to be given a certificate to replace the lost and damaged land rights. This research was conducted using empirical juridical methods that see a statutory regulation as a benchmark and see the facts and phenomena that occur in the field, especially in Merauke. Data is obtained later and processed with primary, secondary and tertiary legal materials. From the results of the research conducted it can be said that the arrangement of the issuance of replacement certificates is clear and well structured. Starting from the highest regulation to the lowest regulation.